Craters on comets. (March 2015) - Vincent, Jean-Baptiste; Oklay, Nilda; Marchi, Simone; Höfner, Sebastian; Sierks, Holger
Abstract: This paper reviews the observations of crater-like features on cometary nuclei. We compare potential crater sizes and morphologies, and we discuss the probability of impacts between small asteroids in the Main Belt and a comet crossing this region of the Solar System. Finally, we investigate the fate of the impactor and its chances of survival on the nucleus. We find that comets do undergo impacts although the rapid evolution of the surface erases most of the features and make craters difficult to detect. In the case of a collision between a rocky body and a highly porous cometary nucleus, two specific crater morphologies can be formed: a central pit surrounded by a shallow depression, or a pit, deeper than typical craters observed on rocky surfaces. After the impact, it is likely that a significant fraction of the projectile will remain in the crater. During its two years long escort of comet 67P/Churyumov–Gerasimenko, ESA׳s mission Rosetta should be able to detect specific silicates signatures at the bottom of craters or crater-like features, as evidence of this contamination. For large craters, structural changes in the impacted region, in particular compaction of material, will affect the local activity. The increase of tensile strength can extinct the activity by preventing the gas from lifting up dust grains. On the other hand, material compaction can help the heat flux to travel deeper in the nucleus, potentially reaching unexposed pockets of volatiles, and therefore increasing the activity. Ground truth data from Rosetta will help us infer the relative importance of those two effects. Abstract : Highlights: We reviewed the observed morphologies of craters on comets. Impact probability is not negligible and some craters can have impact origin. Their peculiar morphology can be explained with existing scaling laws. We studied the effect of porosity with hydrocode numerical simulations. A large fraction of the projectile can survive.